Identificación y evaluación de la susceptibilidad antimicrobiana de bacterias causantes de infección en pacientes con órganos trasplantados del hospital guillermo almenara. 2011-2012 - Requelme Lulichac, Segundo Eduardo (2014)
This study have aim to identify the bacteria causing infection and antimicrobial susceptibility in organ transplant patients at the Hospital Guillermo Almenara, in the city of Lima. Samples were evaluated for transplant patients consisting of urine, catheter, wound secretion, blood, endotracheal aspirate and intraabdominal abscess. Technique was used on primary isolation plate; also blood culture was used for system Versa TREK, Walk Away MicroScan system 96 was used for bacterial identification and to the antimicrobial susceptibility by the Kirby Bauer method. We found 58.4% of bacterial infection, predominant of the urinary tract, the most common bacteria Escherichia coli was 44.7%. In gram-negative bacteria maintaining sensitivity to amikacin, imipenem and meropenem, but moderate to high resistance in the rest of antimicrobials. In gram-positive bacteria, found good sensitivity to the glycopeptides, quinupristin/dalfopristin, tetracycline, rifampicin and linezolid, oxacillin and ampicillin marked resistance encountered. Also was found E. coli and Klebsiella pneumoniae carrying extended spectrum beta-lactamases, whit 45,2% and 45,5% respectivity. Were isolated methicillin-resistant Staphylococcus aureus in 86% and Staphylococcus aureus induced resistance to clindamycin in 14%, not found metallobetalactamase producing bacteria. It is concluded that high frequency of bacterial infection in transplant recipients. E. coli was the most common bacteria and antimicrobial susceptibility is a marked tendency to resistance.